2016
DOI: 10.1007/s13300-016-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Liraglutide in Type 2 Diabetes Treatment in the Real-World Setting: A Systematic Literature Review

Abstract: IntroductionIn clinical trials, liraglutide has proven to be an effective drug for the treatment of type 2 diabetes mellitus (T2DM). The real-world effectiveness of liraglutide has been investigated in numerous studies. The aim of this systematic literature review is to collate evidence on the real-world clinical effectiveness of liraglutide.MethodsA review of publications from Medline, EMBASE, the Cochrane Library, and conference proceedings was conducted to identify observational studies that assessed the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 69 publications
(307 reference statements)
20
47
1
Order By: Relevance
“…These findings are generally consistent with those from other studies and compare favourably with published data for other GLP‐1RAs 1, 6, 7, 21. For instance, a meta‐analysis of seven clinical trials in participants with T2D showed that 32% to 40% of participants receiving liraglutide achieved HbA1c <53 mmol/mol (7.0%) concentrations without weight gain or hypoglycaemia, vs 8% for placebo and 8% to 25% for comparators (exenatide, IGlar, sitagliptin, sulphonylureas or thiazolidinedione) 21.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are generally consistent with those from other studies and compare favourably with published data for other GLP‐1RAs 1, 6, 7, 21. For instance, a meta‐analysis of seven clinical trials in participants with T2D showed that 32% to 40% of participants receiving liraglutide achieved HbA1c <53 mmol/mol (7.0%) concentrations without weight gain or hypoglycaemia, vs 8% for placebo and 8% to 25% for comparators (exenatide, IGlar, sitagliptin, sulphonylureas or thiazolidinedione) 21.…”
Section: Discussionsupporting
confidence: 93%
“…GLP‐1RAs are effective at reducing HbA1c, body weight and inducing satiety 1, 6. Unlike therapy with insulin and sulphonylureas, GLP‐1RAs act by inducing glucose‐dependent insulin secretion and are associated with a low risk of hypoglycaemia and weight gain 1, 6, 7, 8. GLP‐1RAs are generally well tolerated,1 although gastrointestinal (GI) adverse events (AEs) are commonly observed across the class 2, 9…”
Section: Introductionmentioning
confidence: 99%
“…These findings were verified in a recent systematic review of observational data [18]. Real-life clinical data assessed in an audit by The Association of British Clinical Diabetologists (ABCD) demonstrated that, after 6 months of treatment, liraglutide had effectively reduced HbA 1c and was well tolerated [19, 20].…”
Section: Discussionmentioning
confidence: 78%
“…8 It has been approved by the Food and Drug Administration as an adjunct to diet and exercise for management of adult patients with type 2 diabetes. 9 The most common side effects of this medication are nausea and vomiting, which are particularly bothersome for patients during the first few weeks of treatment. 9 Indeed, these gastrointestinal symptoms can at times be severe enough to cause dehydration and precipitate acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…9 The most common side effects of this medication are nausea and vomiting, which are particularly bothersome for patients during the first few weeks of treatment. 9 Indeed, these gastrointestinal symptoms can at times be severe enough to cause dehydration and precipitate acute kidney injury. 10 …”
Section: Discussionmentioning
confidence: 99%